Complete sets of F-squares of order N - Federer, Walter T. (Utilitas Mathematica, 2004)
A number of new concepts and definitions, a method for constructing a complete set of sum-of-squares orthogonal F-squares of order n, and a method of completing a set of combinatorially orthogonal F-squares with sum-of-squares orthogonal F-squares are presented. This new geometry includes the projective geometry for prime powers. Examples for n = 6, 8, 10, 12, 14, 15, and 18 are given to illustrate the concepts and methods.